Musk Tongxin Dripping Pills for treating Ticagrelor in Patients After Percutaneous Coronary Intervention: Echocardiography Combined with Untargeted Metabolomics - Nan, Lyu; Peng, Lai; Jinxia, Zhao; Mengzhe, Guo; Jun, Liang; Haibo, Wang; Houfa, Geng (Frontiers in Pharmacology, 2021)
Objectives: Ticagrelor is the recommended treatment by current clinical practice guidelines to prevent adverse cardiovascular events in acute myocardial infarction (AMI) patients after percutaneous coronary intervention (PCI), but this treatment regimen still fails and 5%-40% patients display inadequate antiplatelet responses. Musk Tongxin Dripping Pill (MTDP) was used as the combination with Ticagrelor to improve the therapeutic effect. However, the mechanism has not been elucidated. Methods: We used the non-targeted metabolomics method based on HPLC-HRMS coupled with STI for the investigation the drug combination mechanism of ticagrelor and MTDP. 28 patients were selected with a definite diagnosis of AMI and divided into two groups with different dosage regimen and the serum samples were collected for the untargeted metabolomics analysis. Then the differential metabolites were associated with blood biochemical indicators. Results: The GLS values in both groups increased after treatment and in drug combination group after treatment were higher than that in ticagrelor group, suggesting that the combination medication has better therapeutic effect on patients with myocardial infarction. From metabolomics analysis, the species of metabolites changed in two groups before and after treatment. Moreover, the species of metabolites also changed in drug combination group by compared with ticagrelor group after treatment, which mainly related to changes in fatty acid metabolism pathways. Then the differential metabolites were found to be related with blood biochemical indicators, such as lipid, high-density lipoprotein (HDL), and low-density lipoprotein (LDL). Conclusion: This work has explained the mechanism of the drug combination between ticagrelor and MTDP from the point of view of metabolic product change, and revealed the potential metabolic pathways it affects, which provided the new ideas for clinical medication.